2020
DOI: 10.1038/s41378-020-00219-w
|View full text |Cite
|
Sign up to set email alerts
|

Using intracellular plasmonics to characterize nanomorphology in human cells

Abstract: Determining the characteristics and localization of nanoparticles inside cells is crucial for nanomedicine design for cancer therapy. Hyperspectral imaging is a fast, straightforward, reliable, and accurate method to study the interactions of nanoparticles and intracellular components. With a hyperspectral image, we could collect spectral information consisting of thousands of pixels in a short time. Using hyperspectral images, in this work, we developed a label-free technique to detect nanoparticles in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…The intracellular plasmonic literature shows a shift dependence of the LSPR Au-based NP band and its subcellular compartment localization. Some studies revealed a band shift of almost 40 nm once they were inside or outside cells . Although this intracellular plasmonic effect probably did not alter the PTT property of our AuNF because of their broad NIR band, as observed in PTT results.…”
Section: Results and Discussionsupporting
confidence: 50%
“…The intracellular plasmonic literature shows a shift dependence of the LSPR Au-based NP band and its subcellular compartment localization. Some studies revealed a band shift of almost 40 nm once they were inside or outside cells . Although this intracellular plasmonic effect probably did not alter the PTT property of our AuNF because of their broad NIR band, as observed in PTT results.…”
Section: Results and Discussionsupporting
confidence: 50%
“…Different responses to nanostars and nanospheres could be associated with different distributions of nanospheres and nanostars in cells. According to the results and our previous study, nanospheres were localized mainly at the periphery of the nucleus where the force is generated and needs to translocate to the adhesion complexes for cell migration, so they could profoundly reduce cell migration compared to nanostars. Different affinities to different subcellular elements may also be an influential factor in the level of impact on mechanobiological properties.…”
Section: Discussionmentioning
confidence: 57%
“…A549 cells appeared to uptake more nanospheres than nanostars over 24 h, likely due to their relatively smaller size. Our previous study shows that A549 cells take up more nanospheres compared to nanostars …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with non-spherical counterparts, spherical NPs have a higher level of internalization ( Sohrabi Kashani et al, 2020 ). Even though nanospheres are promising candidates for drug delivery, anisotropic nanostructures may be more efficient due to larger surface/volume ratios and the ability to deliver higher drug concentrations to the desired regions ( Sun et al, 2014 ).…”
Section: Functional Identification and Tools Of Npsmentioning
confidence: 99%